2018
DOI: 10.1002/ppul.23976
|View full text |Cite
|
Sign up to set email alerts
|

The use of pharmacogenomics, epigenomics, and transcriptomics to improve childhood asthma management: Where do we stand?

Abstract: Asthma is a complex multifactorial disease and it is the most common chronic disease in children. There is a high variability in response to asthma treatment, even in patients with good adherence to maintenance treatment, and a correct inhalation technique. Distinct underlying disease mechanisms in childhood asthma might be the reason of this heterogeneity. A deeper knowledge of the underlying molecular mechanisms of asthma has led to the recent development of advanced and mechanism-based treatments such as bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 136 publications
(291 reference statements)
0
28
0
2
Order By: Relevance
“…As predicted [70], individualized medicine in this first phase which has started now will rather restrict access to drugs than tailor new drugs to individual needs. Using genetic and nongenetic data such as transcriptomics, epigenetics, and metabolomics, asthma and allergy patients may be first characterized as nonresponders to standard therapy as discussed in a previous conceptual paper [71]. In those patients, even though high doses of steroids and other drugs are administered, their disease is not controlled, leading to ever-increasing amounts of drugs with side effects, uncontrolled symptoms, ER visits, and hospital admissions.…”
Section: Genetics and Epigenetics Play A Role In The Response To Clasmentioning
confidence: 99%
“…As predicted [70], individualized medicine in this first phase which has started now will rather restrict access to drugs than tailor new drugs to individual needs. Using genetic and nongenetic data such as transcriptomics, epigenetics, and metabolomics, asthma and allergy patients may be first characterized as nonresponders to standard therapy as discussed in a previous conceptual paper [71]. In those patients, even though high doses of steroids and other drugs are administered, their disease is not controlled, leading to ever-increasing amounts of drugs with side effects, uncontrolled symptoms, ER visits, and hospital admissions.…”
Section: Genetics and Epigenetics Play A Role In The Response To Clasmentioning
confidence: 99%
“…The most important ADRs by consensus for each drug class varied; for beta-2 agonists (SABA or LABA) it was tachycardia, for corticosteroids it was both adrenal suppression/crisis and reduced growth, for LTAs it was sleep/ behaviour disturbances, and for theophylline it was nausea and vomiting. Not all participants completed the survey for (14) Adrenal suppression crisis (11) Sleep/behaviour disturbances (12) Nausea and vomiting (9) Arrhythmias (9) Reduced growth (11) Headache 7Arrhythmias 7Fine Tremor (8) Candidiasis (4) Nausea and vomiting (5) Headache (5) Hypokalaemia 6 ADRs of each drug. For theophylline, 39% reported that the drug was no longer used in current treatment steps.…”
Section: Survey Resultsmentioning
confidence: 99%
“…In addition, a patient’s genotype can affect outcomes of treatment in asthma [ 6 8 ]. The data from these pharmacogenomic studies of asthma medication efficacy in children have progressed to the point where there are now polymorphisms approaching clinical utility [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last year, the role of different omics in asthma treatment response has been recapitulated in different reviews [16][17][18][19][20][21]. This review aims to provide an update on the latest findings in omic studies of pediatric asthma treatment response.…”
Section: Introductionmentioning
confidence: 99%